Mechanical and Morphological Characterization of Hybrid Epoxy Composites Reinforced With Agricultural Waste Fibers - Md. Abdul Hannan Sarker; Md. Shakil Chowdhury; Md. Shah Oliullah; Md. Rubel Ahmed; Md. Zobair Al Mahmud; Habibur Rahman; Ripon Kumar Roy; Nayem Hossain (SPE Polymers)
ABSTRACT This study investigates the mechanical, morphological, and moisture absorption properties of sustainable epoxy composites reinforced with agro‐waste fibers including jute, betel nut husk, corn bark, and sugarcane residues. The composites were fabricated via the hand lay‐up method. Three distinct hybrid composites were fabricated and systematically tested for tensile, flexural, impact, SEM, and water absorption performance. Among the developed composites, the jute + corn bark fiber configuration demonstrated the highest tensile strength (23.60 MPa), flexural strength (21.17 MPa), and strain (8.67%), attributed to superior fiber–matrix adhesion and compact microstructure as validated by scanning electron microscopy (SEM). In contrast, composites reinforced with sugarcane and betel nut fibers exhibited greater porosity, reduced strength, and higher water uptake, highlighting the impact of fiber morphology and interfacial bonding. All samples resisted oil absorption but varied significantly in water and saltwater environments; with the jute + corn bark composite exhibiting the lowest moisture uptake. The findings confirm the viability of underutilized agro‐waste fibers—particularly corn bark—as promising reinforcements in cost‐effective, biodegradable composites suitable for non‐load‐bearing construction, packaging, acoustic insulation, and automotive interior applications. This study is the first to investigate the use of jute fabric reinforced with corn bark fibers in epoxy composites, revealing their superior performance compared to betel nut and sugarcane fibers. The findings advance the field of green materials engineering by offering a sustainable alternative to synthetic composites, particularly suited for moisture‐sensitive and moderately demanding structural applications.